Older adults coping with critical life events - results of the revised demoralization scale in a representative sample of older adulthood - Ramm, Markus; Jedamzik, Johanna; Lenz, Philipp; Jürgens, Lara; Heuft, Gereon; Conrad, Rupert (Frontiers in Psychiatry, 2024)
High suicide rates in older adults are a relevant public health concern. Social isolation or widowhood as well as physical decline play a crucial role for suicidality in older adulthood. Previous evidence suggested that demoralization is an important risk factor for suicide. Whether demoralization is a relevant phenomenon in older adulthood which possibly could account for high suicide rates remains unclear.DS-II scores assessed in a survey of the German general population were investigated with respect to older adults (aged > 65 years). DS-II scores were compared between older (> 65 years) and younger (< 65 years) adulthood and between young-old (65-74y), middle-old (75-84y), and old-old (85+y) individuals. We tested the impact of sociodemographic factors on DS-II scores within older adults.The sample comprised N = 545 adults ≥ 65 years and N = 1922 adults < 65 years. DS-II scores increased in older compared to younger adults (F(1,2465) = 6.1; p = 0.013; d = 0.09) and further from young-old to old-old (Mdiff = 2.7; 95% CI 0.45, 5.46; p = 0.034). One-fourth of individuals ≥ 65 years and almost half of old-old individuals reported DS-II scores above the cut-off > 5. Living with a partner protected from demoralization in old-old individuals.This study provides first evidence for an increased rate of demoralization in very old adults, in particular women, which is partly related to partnership status. We suggest that demoralization is considered as a crucial entity in older adulthood which can be missed by standard psychological screenings.